The cryoprotectant PVS2 plays a crucial role in germinating Passiflora ligularis embryos after cryopreservation by influencing the mobilization of lipids and the antioxidant metabolism - Oliveira Prudente, D. de; Paiva, R.; Domiciano, D.; Souza, L.B. de; Carpentier, Sebastien C.; Swennen, Rony L.; Silva, L.C.; Nery, F.C.; Máximo, W.P.F.; Panis, Bartholomeus (Elsevier, 2019)
Cryopreservation is a process whereby biological structures are preserved in liquid nitrogen (−196 °C) without losing their viability. Many cryopreservation techniques use the Plant Vitrification Solution 2 (PVS2) for cryoprotection. This study will therefore evaluate the influence of different exposure times to the cryoprotectant PVS2 and discuss the importance of the mobilization of reserves and the antioxidant metabolism during the germination of cryopreserved Passiflora ligularis embryos. The composition of P. ligularis seeds was analytically determined. We tested the germination capacity and the Germination Speed Index (GSI) of embryos (that is, seeds without external tegument) which were exposed to different PVS2 exposure times (0, 30, 60 and 120 min) at 30 days after thawing. Proline content, hydrogen peroxide, activity of isocitrate lyase (ICL), malate synthase (MSy), lipid peroxidation and antioxidant enzyme activities (SOD, CAT, APX) were measured at 7, 14 and 21 days after cryopreservation. The germination from cryopreserved embryos was maximal (85%) after 60 min PVS2 exposure with a GSI of 0.6. At 60 min, the highest activity of the enzymes involved in the glyoxylate cycle, ICL and MSy were recorded. We hypothesize that a 60 min exposure to PVS2 accelerates the reserve mobilization which correlates positively with germination. Until 60 min, there was a positive correlation between the PVS2 exposure time and the proline content, as well as the activity of antioxidant enzymes (SOD, CAT, APX), and a negative correlation with the lipid peroxidation. This study enables us to optimize the long-term conservation of this species. In conclusion, fundamental research is necessary to optimize the cryopreservation procedure, and this study offers an effective and efficient workflow which can be extrapolated to other (oil-rich) species.